Neoadjuvant nivolumab for patients with resectable HPV-positive and HPV-negative squamous cell carcinomas of the head and neck in the CheckMate 358 trial. Issue 6 (2nd June 2021) - Ferris, Robert L; Spanos, William C; Leidner, Rom; Gonçalves, Anthony; Martens, Uwe M; Kyi, Chrisann; Sharfman, William; Chung, Christine H; Devriese, Lot A; Gauthier, Helene; Chiosea, Simon I; Vujanovic, Lazar; et al.
Abstract : Background: Head and neck squamous cell carcinomas (HNSCCs) are common malignancies caused by carcinogens, including tobacco and alcohol, or infection with human papillomavirus (HPV). Immune checkpoint inhibitors targeting the programmed cell death 1 (PD-1) pathway are effective against unresectable recurrent/metastatic HNSCC. Here, we explored the safety and efficacy of anti-PD-1 therapy in at-risk resectable HPV-positive and HPV-negative HNSCC in the neoadjuvant setting. Methods: The phase I/II CheckMate 358 trial in virus-associated cancers assessed neoadjuvant nivolumab in patients with previously untreated, resectable HPV-positive or HPV-negative HNSCC. Patients received nivolumab 240 mg intravenously on days 1 and 15, with surgery planned by day 29. Safety/tolerability (primary endpoint) was assessed by monitoring adverse events (AEs) and surgical delays. Radiographic response was measured before surgery using RECIST v1.1, adapted for a single post-nivolumab evaluation. Pathologic specimens were examined for treatment response using immune-based criteria. Results: From November 2015 to December 2017, 52 patients with AJCC (seventh edition) stage III–IV resectable HNSCC received neoadjuvant nivolumab (26 HPV-positive, 26 HPV-negative). Any-grade treatment-related AEs (TRAEs) occurred in 19 patients (73.1%) and 14 patients (53.8%) in the HPV-positive and HPV-negative cohorts, respectively; grade 3–4 TRAEs occurred in five (19.2%) and three patients (11.5%), respectively. No patient had a protocol-defined TRAE-related surgical delay (>4 weeks). Thirty-eight patients were reported as undergoing complete surgical resection, 10 had a planned post-nivolumab biopsy instead of definitive surgery due to a protocol misinterpretation, and four did not undergo surgery or biopsy, including two with tumor progression. Radiographic response rates in 49 evaluable patients were 12.0% and 8.3% in the HPV-positive and HPV-negative cohorts, respectively. There were no complete pathologic responses by site or central review in operated patients. Among 17 centrally evaluable HPV-positive tumors, one (5.9%) achieved major pathological response and three (17.6%) achieved partial pathologic response (pPR); among 17 centrally evaluable HPV-negative tumors, one (5.9%) achieved pPR. Conclusions: Neoadjuvant nivolumab was generally safe and induced pathologic regressions in HPV-positive (23.5%) and HPV-negative (5.9%) tumors. Combinatorial neoadjuvant treatment regimens, and continued postoperative therapy for high-risk tumors, are warranted in future trials to enhance the efficacy of this approach. Trial registration number: ClinicalTrials.gov NCT02488759 ; https://clinicaltrials.gov/ct2/show/NCT02488759 .